PHYSICAL MODEL OF WORK OF THE SYSTEM «METAL PRELIMINARY TENSION REINFORCEMENT JACKET - DAMAGED REINFORCED CONCRETE BEAM» (Collection of scientific works «Modern structures of metal and wood», 2020)
Analysis  of  the  damage  responsible  for  the  vital  activity  of  a  span  reinforced concrete structure, structure or building,  in general, showed that during their operation there  is a significant  destruction  of  the  concrete  protective  layer,  corrosion  of  the  reinforcement,  crack formation and excessive opening, achievement of unacceptable deflections, etc. The aim of this work is to experimentally and theoretically study physical models reinforced with  prestressed  metal  jackets  damaged  by  through  normal  and  transverse-inclined  cracks  in reinforced concrete beams under active low-cycle alternating loads of high levels. To this end, a method was created for the restoration of damaged reinforced concrete beams needed  in  an  anticipated  state,  as  a  result  of  which  alternating  cyclic  or  pulsating  loads  of  high levels arise, and a device for providing it. All tested beam samples were manufactured and tested in accordance with the experimental design theory and D-optimum plan of Box B4. The accomplished system approach to the experimental and theoretical research of the stress-strain  behaviour  of  the  common,  renewed  and  strengthened  reinforced  concrete  span  structures damaged  with  through  forced  cracks  with  the  aid  of  metal  prestressed  metal  casings  enabled  to make  a  reliable  quantitative  and  qualitative  evaluation  of  the  design  factors  and  external  factors impact on their load-bearing capacity, stiffness, crack resistance and other performance parameters, either individually or in their interaction with each other, considerably specify the physical model of said structures performance when subjected to static and low-cycle alternate loading. The  experiments  have  proved  a  possibility  and  expediency  of  practical  application  of  the ingenious method developed by the authors which is distinctive of renewal and strengthening of the damaged  reinforced  concrete  beam  structures  damaged  with  through  normal  and  cross  inclined cracks which divide the beam into separate blocks due to three-side clamping, and the arrangement for  its  accomplishment  claimed  by  the  patent  of  invention  subjected  to  action  of  the  increasing static,  cyclic,  alternate,  seismic,  fluctuating  and  other  dynamic  loading,  including,  among  other things, the reinforced concrete beams damaged during military activity provide such beams did not collapse completely and preserve their initial shape.